Carbon Emissions, Energy Consumption, and Economic Growth in Morocco - Benali, Mimoun; Benabbou, Laila (International Journal of Energy Economics and Policy, 2023)
This study examines the relationship between carbon emissions, energy consumption, and economic growth in Morocco from 1990 to 2021. The ARDL technique was employed to analyze the long and short-term relationships among the variables. Results reveal a long-term relationship between carbon emissions, energy consumption, and economic growth in Morocco. Additionally, economic growth was found to have a positive and significant impact on carbon emissions both in the short and long term, supporting the Environmental Kuznets Curve hypothesis. Policymakers and governments must prioritize investments in energy efficiency improvements and carbon emissions reductions through effective environmental policies and infrastructure investments while emphasizing alternative and renewable energy sources.